WAYS TO INCREASE THE ECONOMIC EFFICIENCY OF TEXTILE EXPORTS - Ulmasova Shakhnoza Khislatovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: The textile industry is considered one of the main sectors in the economy of each country. This network is actively developing not only on the basis of domestic needs, but also on the basis of external market requirements. At the moment, the priority is to achieve the economic stability of the country through the export of textile products, increase revenues from exports and increase foreign currency revenues. At a time of increasing competition in the global market, it is required to introduce new approaches to effectively organize exports and increase profits. In achieving economic efficiency, a systematic approach is important in technological modernization, quality management, improvement of the logistics system, modernization of marketing strategies and state support.